PERAN GURU PAIBP DALAM PEMBERIAN BIMBINGAN DAN KONSELING DI SDN BABAKAN SUKAMULYA KABUPATEN BANDUNG - Aryani Dyah Aryani; Iwan Anggara Nova; Samsudin Arif; Arif Fikri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2023)
Guidance and counseling are very important in providing the basics of religion and character for elementary school students. The aim of the study was to determine the role of Islamic religious education and morals (IREM) teachers in providing Guidance and Counseling. This study uses a descriptive qualitative approach, and data collection through interviews, observation and document study. The results of the study show that the role of IREM teachers is in providing guidance and counseling to students through personal, social, career and learning guidance. Personal guidance through habituation in attitude and speech, advice and giving exemplary examples. Social guidance, namely providing an understanding of how to communicate and interact with the social environment and school regulations. Career guidance, namely providing stimulus and introduction to advanced levels of education. Learning guidance, namely providing motivation and special services for students who experience problems in learning. Keywords: Role of IREM Teachers, Counseling Guidance, Elementary Schools